2015
DOI: 10.1016/j.biortech.2014.11.068
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a screening procedure of microalgae for biodiesel production: Application to the genus of marine microalgae Nannochloropsis

Abstract: Nannochloropsis has emerged as a promising alga for biodiesel production. However, the genus consists of 6 species and hundreds of strains making strain selection a challenge. Furthermore, oil productivity is instrumental to economic viability of any algal strain for industrial production, which is dependent on growth rate and oil content. In most cases, these two parameters have been studied independently. Thus, the goal of this study is to provide a combined method for evaluating strain performance in specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 29 publications
(41 reference statements)
4
47
0
1
Order By: Relevance
“…It consisted of six small-scale photobioreactors (bubble columns) run in parallel, each tube having a volume V r = 3 · 10 −5 m 3 , an illuminated area of S L = 0.008 m 2 and a specific illuminated area of a light = S/V r of 266.7 1/m. A full description of the EOSS-PBR is done in Taleb et al [18].…”
Section: Culture Medium Screening In Efficient Overproducing Screeninmentioning
confidence: 99%
See 1 more Smart Citation
“…It consisted of six small-scale photobioreactors (bubble columns) run in parallel, each tube having a volume V r = 3 · 10 −5 m 3 , an illuminated area of S L = 0.008 m 2 and a specific illuminated area of a light = S/V r of 266.7 1/m. A full description of the EOSS-PBR is done in Taleb et al [18].…”
Section: Culture Medium Screening In Efficient Overproducing Screeninmentioning
confidence: 99%
“…Before inoculation, the culture medium was filtered through a 0.45 μm pore size filter to remove undesirable small particles. The pH in the culture medium was around 7.5 for the freshwater microalgae species and 8 for the marine microalgae species, according to Pruvost et al and Taleb et al [17,18]. The culture agitation was provided by continuous injection of air with 2 vol.% CO 2 at a flow rate of 3 mL/min; the incident photon flux density (PFD), by a set of 6 fluorescent white tubes was~150 μmol/m 2 ·s.…”
Section: Culture Medium Screening In Efficient Overproducing Screeninmentioning
confidence: 99%
“…Some of the challenges include the wide biodiversity of microalgae and the dependency of their photosynthetic activity and especially their lipid metabolism on their cultivation conditions. Previously, Taleb et al, (2015) showed that TAG accumulation capacity cannot be the only criterion used to select the ideal strain. Many species are well known to accumulate large amount of neutral lipids and TAGs in nitrogen starvation conditions .…”
Section: Introductionmentioning
confidence: 99%
“…TAG) can be quantified [3840] should be routinely adopted. The predictability of such high-throughput screenings should be validated at lab scale with the selected strains and processes should be developed under simulated outdoor production conditions [34]. Finally, the selected strains should be tested outdoors in pilot PBRs under relevant climate conditions [24, 41, 42].…”
Section: Discussionmentioning
confidence: 99%